Hardiness and Culture: A Study with Reference to the 3 Cs of Kobasa - Mund, Pallabi (International Research Journal of Management, IT & Social Sciences, 2017)
The concept of Hardiness was first given by Suzanne C. Kobasa (1979) as a personality style or pattern associated with continued good health and performance under stress. According to her, hardy people are buffered against stressful life situations because they engage in certain affective, cognitive, and behavioral responses. In her foundational paper entitled âStressful life events, personality, and health: An inquiry into hardinessâ, published in the Journal of Personality and Social Psychology in 1979, Suzanne C. Kobasa introduced the concept of psychological hardiness and suggested that hardiness moderates the relationship between stressful life events and illness. Kobasa characterized hardiness as comprising of three components or the 3Câs: Commitment, Control, and Challenge. This paper is an attempt to study these hardiness components and the subsequent additions to the research work in the area of study made by such succeeding scholars as Salvatore R. Maddi, S. Kahn, Paul T. Bartone, W. D. Gentry, et al. In 2005, Maddi added Connection as the 4th C and in my paper I have proposed Culture as the 5th C, a component relevant especially to the Indian context.